Aktivitas Forwarded Messages pada Pengguna WhatsApp di Berbagai Usia dan Gender - Nona Evita; Helen Helen; Ivan Widjanarko (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
Almost all Indonesian people currently use WhatsApp. The number of users of this instant messaging application makes Indonesia the third largest WhatsApp user in the world. Not just for chatting, Indonesian people currently use WhatsApp for many things, one of which is sharing news or information through forwarded messages. Previous research has shown that forwarded messages activity on WhatsApp is prone to hoaxes. Similar research has also been done, but to see activity in general, not specific to the activity of forwarded messages. Therefore, this study wants to fill this void by looking at forwarded messages activity across different ages and genders. Using the decision tree method and the Bayesian network algorithm, this study analyzed 63 documents of the participant's WhatsApp group conversation history. This study found that generation X and baby boomers are the two generations who send the most forwarded messages on WhatsApp. Meanwhile, related to gender, researchers did not find a significant difference in forwarded messages activity.